Supplementing rainbow trout (Oncorhynchus mykiss) broodstock diets with choline and methionine improves growth in offspring. Issue 1 (20th June 2019) - Cleveland, Beth M.; Leeds, Timothy D.; Picklo, Matthew J.; Brentesen, Carley; Frost, Jason; Biga, Peggy R.
Abstract: Nutritional programming represents the mechanism through which broodstock feeding strategies have lifelong effects on the offspring generation. The objective of this study was to determine whether supplementing rainbow trout, Oncorhynchus mykiss broodstock diets with choline and methionine affects offspring growth performance. Experimental diets were produced by top‐dressing a commercial broodstock diet with (a) 12, 000 ppm methionine, (b) 7, 400 ppm choline, (c) 12, 000 ppm methionine and 7, 400 ppm choline, or (d) water (control). Six rainbow trout families were fed experimental diets beginning 18 months post‐hatch through spawning; the offspring consumed a commercial diet. The broodstock diet did not affect maternal body weight, body condition, egg size, or egg yield ( p > .05). Eggs from choline‐treated broodstock contained 10% more choline than control eggs ( p < .05). Offspring from choline‐treated broodstock were smaller than controls at 146 days post‐hatch (dph) ( p < .05). At the final harvest (439 dph), offspring from the control broodstock weighed 12–18% less than offspring from broodstock consuming the supplemented diets ( p < .05). However, there was a significant diet‐by‐family interaction on offspring growth ( p < .05); supplemented diets improved performance in three of the six broodstock families. These findings indicate that supplementing broodstock diets with methionine and choline causes a nutritional programming effect that benefits growth in offspring.